2016
DOI: 10.1186/s13075-016-1169-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin landscapes and genetic risk in systemic lupus

Abstract: BackgroundSystemic lupus erythematosus (SLE) is a multi-system, complex disease in which the environment interacts with inherited genes to produce broad phenotypes with inter-individual variability. Of 46 single nucleotide polymorphisms (SNPs) shown to confer genetic risk for SLE in recent genome-wide association studies, 30 lie within noncoding regions of the human genome. We therefore sought to identify and describe the functional elements (aside from genes) located within these regions of interest.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…These data have implicated T cells (CD4 > CD8), B cells, and monocytes in SLE. One study utilizing neutrophil ChIP-seq data found enrichment of genes with potential ETS TF binding near SLE GWAS SNPs ( 27 ). To our knowledge, there are no previous studies that have used disease-related changes in RNA and H3K4me3 to analyze GWAS variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data have implicated T cells (CD4 > CD8), B cells, and monocytes in SLE. One study utilizing neutrophil ChIP-seq data found enrichment of genes with potential ETS TF binding near SLE GWAS SNPs ( 27 ). To our knowledge, there are no previous studies that have used disease-related changes in RNA and H3K4me3 to analyze GWAS variants.…”
Section: Discussionmentioning
confidence: 99%
“…95 SNP with GWAS p -values less than 1E-8 were selected from a study of 1,311 SLE patients ( 26 ). Additionally, a set of 46 SNPs ( 27 ) curated from two published studies was used ( 28 , 29 ) and this is referred to as LD46 and a set of 25 SNPs curated from a meta-analysis of 7,219 SLE cases was used and referred to as META25 ( 28 ). All three sets of SNPs were used to generate a joint set of 143 SNPs used for analyzing RNA-seq data.…”
Section: Methodsmentioning
confidence: 99%
“…When these SNPs are associated with changes in gene expression, termed eQTLs, they can be used to implicate cell types that are likely to play a role in disease, such as T-cell genes in RA and B cells in lupus [ 86 , 87 ], although the underlying mechanism is not always clear. To uncover the molecular link between SNPs and disease, two studies which used data from genome-wide association studies (GWAS) and chromatin assays of multiple cell types found were able to implicate high-confidence causal SNPs that have the potential to disrupt regulatory elements [ 88 – 90 ]. But these studies, limited as they are by the sensitivity of GWAS and generic chromatin profiles from unrelated donors, are just the beginning.…”
Section: Main Textmentioning
confidence: 99%
“…(1) most of the tag SNPs that identify risk regions are located in non-coding regions of the genome [ 6 ]; and (2) these regions are highly enriched for non-coding elements such as enhancers [ 7 , 8 ]. The reverse is also true: if one maps enhancer elements in specific cell types, those mapped regions are highly enriched in GWAS-identified SNPs for diseases that affect those particular cells or tissues [ 9 ].…”
Section: Introductionmentioning
confidence: 99%